Peningkatan Kemampuan Menulis Cerpen dengan Metode Sigap Siswa Kelas IXE Semester Gasal SMP Negeri 40 Semarang Tahun Ajaran 2021/2022 - Adi Harwanto (Jurnal Inovasi Pembelajaran di Sekolah, 2023)
In general, this study aims to improve students' ability to write short stories in class IX SMP. To achieve this goal, the Sprightly research method (emotion, fast motion, and revision) is used. This research is a class action research (CAR) conducted in two cycles. The results of this study indicate that the learning process and students' ability to write short stories increases after the teacher applies the Sigap method. Student learning outcomes in pre-cycle, cycle I and cycle II also increased, namely 9%, 34%, and finally 66%.